Urgensi Filologi dalam Penyebaran Islam dan Bahasa Arab - Nurul Fahmi (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2017)
Abstract: Philology is a knowledge which discuss about the ancient text’s in form of spoken and written, both of hand or print writing. This article is a library research which will extend about philology in Islamic expansion and Arabic language. The researcher takes two sample cases at Marah Labib ( al-Tafsir al-Munir ) book written by Syekh Nawawi and the story of Syekh Ihsan with his masterpiece, Siraj al-Talibin. Without a philology research, so the problem in two sample cases mentioned will continue in a long time.Keywords: Filologi, Islam, ArabicLanguage.